Effect of Spatial Distribution of nZVI on the Corrosion of nZVI Composites and Its Subsequent Cr(VI) Removal from Water - Yixuan Li; Shuangqiu Huang; Yaqin Song; Xinfang Zhang; Sijia Liu; Qiong Du (Nanomaterials, 2022)
There have been many studies on contaminant removal by fresh and aged nanoscale zero-valent iron (nZVI), but the effect of spatial distribution of nZVI on the corrosion behavior of the composite materials and its subsequent Cr(VI) removal remains unclear. In this study, four types of D201-nZVI composites with different nZVI distributions (named D1, D2, D3, and D4) were fabricated and pre-corroded in varying coexisting solutions. Their effectiveness in the removal of Cr(VI) were systematically investigated. The results showed acidic or alkaline conditions, and all coexisting ions studied except for H2PO4− and SiO32− enhanced the corrosion of nZVI. Additionally, the Cr(VI) removal efficiency was observed to decrease with increasing nZVI distribution uniformity. The corrosion products derived from nZVI, including magnetite, hematite, lepidocrcite, and goethite, were identified by XRD. The XPS results suggested that the Cr(VI) and Cr(III) species coexisted and the Cr(III) species gradually increased on the surface of the pre-corroded D201-nZVI with increasing iron distribution uniformity, proving Cr(VI) removal via a comprehensive process including adsorption/coprecipitation and reduction. The results will help to guide the selection for nZVI nanocomposites aged under different conditions for environmental decontamination.